(untitled) - Gordon, Jon (Hoboken, N.J, 2015)
Winning Strategies Practiced on the Field, Practicable Everywhere The Atlanta Falcons had a 4-12 record without back to back winning seasons. Under Mike Smith's leadership, the Falcons earned an 11-5 record and perennial playoff and Super Bowl contention. The wins from his first five seasons as head coach of the Atlanta Falcons were only surpassed by Bill Belichick and the New England Patriots. And when Mike left, the Atlanta Falcons only won ten games in the two following seasons. You Win in the Locker Room First combines the extraordinary experiences of Mike Smith and Jon Gordon, consultant to numerous college and professional teams, to bring you seven powerful principles to revitalize your business, school, organization, or sports team. You Win in the Locker Room First provides leaders of all fields with a practical framework and real world examples to build a great culture, lead with the right mindset and approach, create strong relationships, improve teamwork, execute at a higher level, and avoid the pitfalls that sabotage far too many leaders and organizations. You Win in the Locker Room First candidly shares tales of striving for success, what went right, what went wrong, and what leaders can learn from these experiences in order to build a winning team.
Keywords: Leadership,Lãnh đạo